Conceptualising and researching the professionalisation of Religious Education teachers: historical and international perspectives. Issue 2 (3rd May 2016) - Freathy, Rob; Parker, Stephen G.; Schweitzer, Friedrich; Simojoki, Henrik
Abstract : Current discussions on Religious Education (RE), both in Germany and England, focus on the quality of teaching and the professionality of teachers, but neglect the historical and institutional process of professionalisation upon which conceptions of teaching quality and teacher professionality hinge. This article seeks to provide definitional clarity by differentiating between individual and collective professionalisation; exploring teacher professionalisation in general and in the special case of RE; and operationalising the concept of RE teacher professionalisation for the purposes of planned historical and international comparative research. A threefold conceptualisation of professionalisation is proposed, consisting of the following inter-related levels: (1) initial and continuing professional development; (2) professional self-organisation and professional politics; and (3) professional knowledge. The breadth, complexity and significance of the historical and institutional processes associated with the professionalisation of RE teachers at each of these levels is described and discussed. It is argued that further historical and international comparative research on these lines would contribute a broader and deeper understanding of the presuppositions of RE teacher professionality beyond current debates.